EMBERIAN VARIASI JENIS PAKAN TERHADAP PERTUMBUHAN BENIH IKAN ARWANA (Scleropages formosus) DI DALAM WADAH BUDIDAYA - Yahya Yahya; Untung Bijaksana; M. Adriani (Fish Scientiae, 2019)
This study aims to determine the feed Arowana fish seed (Scleropagesformosos) after feeding egg yolk tobe variations between, mosquito larvae bloodworms-mosquito larvae(A), crickets-mosquito larvae-crickets(B), and bloodworms-crickets- blood worms(C), are maintained in the container cultivation.Overall implemented for ±5 months from January 2013 to May 2013 in the month of PT. Kresna Pusaka Tirta Lestari Jln. Kuripan. No. 19D RT. 33, Eastern District of Banjarmasin, Banjarmasin, South Kalimantan Parameters observed; Growth Relative Weight, Length Relative Growth, FeedConversion, Survival. Aperture mouth, Out of Egg Yolk longtime, and parameterWater Quality For Supporting Data.From the data obtained during the study relative weight of the highest growthratein treatment B (87.78%), and the lowest was intreatment C (83.98%). The mean length of the highest relative growth in treatment A (30.56%), and the lowest was intreatment C (30.44%). The highest feed conversion intreatment B (1,55%), and thelowest was intreatment A (0,59%). The highest survival rate in treatment A (93.33%),followed bytreatment B (91.52%), andthe lowest was intreatment C(86.67%). Theaverage opening mouth highest in treatment A (58.849), followed involves the B(54.922), and the lowest was intreatment C (51.413). Long arowana depleted eggyolks from the eggs pots(TBK) to egg a big body (TBB) is 13 days, from TBB to swimegg (TBR) 15 days, and from plain eggs to TBR 14 days, so the totalis 42 days. Waterquality during the study ranged between temperature 30-32° C, pH73.77, salinity 0.10- 0.18 ppt, and ammonia from 0.13 - 0.18mg/l .Based on the analysis of variance (ANOVA) on all treatments only on survivaland feed conversion were significantly different, followed by HSD test for survivaland Duncan test for feed conversion. Judging from the data is the best overall treatment A with variations of mosquito larvae-bloodworms-mosquito larvae.